Associations of transcranial doppler velocity, age, and gender with cognitive function in children with sickle cell anemia in Nigeria. Issue 6 (18th August 2019) - Prussien, Kemar V.; Salihu, Auwal; Abdullahi, Shehu U.; Galadanci, Najibah A.; Bulama, Khadija; Belonwu, Raymond O.; Kirkham, Fenella J.; Yarboi, Janet; Bemis, Heather; DeBaun, Michael R.; Compas, Bruce E.
ABSTRACT: Children with sickle cell anemia (SCA) have elevated cerebral blood velocity relative to healthy peers. The primary aim of this study was to evaluate the association between cerebral blood velocity, measured by transcranial Doppler (TCD) ultrasound, age, and gender with cognitive function in children with SCA in Nigeria. Eighty-three children ( M age  = 9.10, SD  = 1.90 years; 55% female) with SCA in Nigeria completed cognitive assessments and a TCD ultrasound. The association between TCD velocity and measures of perceptual reasoning (Raven's Progressive Matrices), working memory (WISC-IV Digit Span), and executive planning (Tower of London, TOL) were assessed. Results showed that elevated TCD velocity significantly predicted lower scores on TOL Time Violations and Total Problem-Solving Time when controlling for BMI, hemoglobin level, and parent education, suggesting that TCD velocity is related to the efficiency of executive function. Further, age was negatively related to children's performance on the Ravens Matrices and TOL Total Correct, and boys showed greater deficits on the TOL Total Correct relative to girls. Moderation analyses for gender showed that there was a conditional negative association between TCD velocity and Digit Span for boys, but not for girls. Findings suggest that children with SCA in Nigeria with elevated TCD velocity are at risk for deficits in efficiency of executive planning, and boys with elevated TCD velocity are particularly at increased risk for deficits in auditory working memory. Implications of this study are important for interventions to reduce cerebral blood velocity and the use of TCD in this population.